Adaptive Dual-Polarization Filtering Method for Countering Active Jamming - Qiang Zhang; Rui Zhou; Xianbo Shi; Yixin Zhao (International Journal of Antennas and Propagation)
In order to counter active jamming, an adaptive polarization filtering method based on dual polarization radar is put forward. First, the signal flow principle of the dual polarization radar and its signal model are introduced. Then, the weighted coefficient matrices of the polarization filter are calculated adaptively according to the actual work situation of the current radar. Finally, the specific polarization filtering algorithm and the output criterion of the optimal filtering results are given. Experimental results show that this method does not need to know the type, quantity, combination mode, polarization characteristics, and other prior knowledge of active jamming but has well effect on both active deception jamming and active blanket jamming, so it has strong engineering application value.